Pengaruh Latihan Kaki Dengan Teknik Romanian Deadlift Terhadap Kemampuan Aktivitas Sehari-Hari Pada Pasien Gout Artritis Di Puskesmas Gribig Kabupaten Kudus - Sukarmin Sukarmin; Amalia Rahmawati; Dwi Pujilestari; Shizuoka Aryoni (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
Background : The World Health Organization (2016) states that gout sufferers worldwide have reached 335million. Gout Arthritis is a disease characterized by sudden, recurrent and painful attacks due to the presence of monosodium urate crystal deposits or uric acid that collect in the joints as a result of high levels of uric acid in the blood / hyperuricemia that can cause pain. Objective : This study aims to determine whether there is an effect of leg training with the Romanian deadlift technique on daily activities in arthritis gout patients.Method : This type of research used Quasi Experiment Design with a pretest-posttest control design group design with one type of treatment, using a sampling technique take by Non Probability Sampling with purposive sampling method with a sample size of 38 respondents, 19 respondents in the intervention group and 19 respondents in the control group. Collecting data using a questionnaire sheet and leg training interventions with the Romanian deadlift technique.Results : This type of research used Quasi Experiment Design with a pretest-posttest control design group design with one type of treatment, using a sampling technique. The results of the study using the Wilcoxon test showed that the p value was 0.000 (p <0.05) and the dependent test was the p value of 0.008. (p <0.05).Consclusion : There is an effect of leg training with the romanian deadlift technique on the ability of daily activities in arthritis gout patients at Puskesmas Gribig, Kudus Regency.